Transcriptional coordination of physiological responses in Nannochloropsis oceanica CCMP1779 under light/dark cycles. (20th August 2015) - Poliner, Eric; Panchy, Nicholas; Newton, Linsey; Wu, Guangxi; Lapinsky, Andrew; Bullard, Blair; Zienkiewicz, Agnieszka; Benning, Christoph; Shiu, Shin‐Han; Farré, Eva M.
Summary Nannochloropsis oceanica CCMP1779 is a marine unicellular stramenopile and an emerging reference species for basic research on oleogenic microalgae with biotechnological relevance. We investigated its physiology and transcriptome under light/dark cycles. We observed oscillations in lipid content and a predominance of cell division in the first half of the dark phase. Globally, more than 60% of the genes cycled in N. oceanica CCMP1779, with gene expression peaking at different times of the day. Interestingly, the phase of expression of genes involved in certain biological processes was conserved across photosynthetic lineages. Furthermore, in agreement with our physiological studies we found the processes of lipid metabolism and cell division enriched in cycling genes. For example, there was tight coordination of genes involved in the lower part of glycolysis, fatty acid synthesis and lipid production at dawn preceding lipid accumulation during the day. Our results suggest that diel lipid storage plays a key role for N. oceanica CCMP1779 growth under natural conditions making this alga a promising model to gain a basic mechanistic understanding of triacylglycerol production in photosynthetic cells. Our data will help the formulation of new hypotheses on the role of cyclic gene expression in cell growth and metabolism in Nannochloropsis.